Comparative Analysis of Deterministic and Nondeterministic Decision Trees for Decision Tables from Closed Classes - Ostonov, Azimkhon; Moshkov, Mikhail (Entropy (Basel, Switzerland), 2024)
In this paper, we consider classes of decision tables with many-valued decisions closed under operations of the removal of columns, the changing of decisions, the permutation of columns, and the duplication of columns. We study relationships among three parameters of these tables: the complexity of a decision table (if we consider the depth of the decision trees, then the complexity of a decision table is the number of columns in it), the minimum complexity of a deterministic decision tree, and the minimum complexity of a nondeterministic decision tree. We consider the rough classification of functions characterizing relationships and enumerate all possible seven types of relationships.